Analisis Profitabilitas atau Rentabilitas (Lembaga Pengembangan Kinerja Dosen, 2025)
Financial statements serve as a crucial communication tool to convey a company's financial performance to investors and other stakeholders. One of the primary analytical tools used in evaluating financial performance is the profitability ratio. This ratio reflects a company’s ability to generate profit from its operational activities, indicating the efficiency of asset and capital management. The types of profitability ratios include Gross Profit Margin, Net Profit Margin, Return on Assets (ROA), Return on Investment (ROI), Return on Equity (ROE), Operating Profit Margin, and Operating Ratio. Each ratio offers unique insights into a company's financial strength. This research uses a library research method and identifies various factors influencing profitability levels, such as capital structure, sales growth, company size, working capital, Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR). The study concludes that profitability ratios are key indicators in assessing financial performance and play a vital role in investment decision-making.